UTILITARIANISME ALASAN EFISIENSI DALAM PEMUTUSAN HUBUNGAN KERJA (PHK) (Studi Putusan No.259/Pdt.Sus-PHI/2020/PN Jkt.Pst) - Muhamad Angga Akbari (2022)
This study aims to find out how the legal benefits of using efficiency reasons in termination of employment are not followed by company closure. Specifically, it aims to: first, find out how the legal benefits of using efficiency reasons in termination of employment are not followed by reasons for closing the company based on Law No. 11 of 2020 concerning Job Creation, secondly knowing the impact suffered by the company doing this. This research method is normative juridical by using a law approach and a conceptual approach. The results of the study show that the practice of using efficiency reasons as the basis for termination of employment by companies can no longer be interpreted as a company that has to close permanently or stop operating which will have implications for layoffs and increasing unemployment, coupled with an imbalance in the availability of employment opportunities. and also has an impact on the receipts or wages received by workers. The formulation of the use of efficiency reasons which can now be carried out without being followed by the company's closing according to the Ciptaker Law is deemed not to have fulfilled the aspects/concepts of good governance which should have not been able to provide protection and welfare that is shown in the interests of all citizens, even tends to provide a sense of security for entrepreneurs only.